Vasoactive intestinal peptide promotes secretory differentiation and mitigates radiation-induced intestinal injury - Agibalova, Tatiana; Hempel, Anneke; Maurer, H. Carlo; Ragab, Mohab; Ermolova, Anastasia; Wieland, Jessica; Waldherr Ávila de Melo, Caroline; Heindl, Fabian; Giller, Maximilian; Fischer, Julius Clemens; Tschurtschenthaler, Markus; Kohnke-Ertel, Birgit; et al. (Stem cell research & therapy, 2024)
Background Vasoactive intestinal peptide (VIP) is a neuronal peptide with prominent distribution along the enteric nervous system. While effects of VIP on intestinal motility, mucosal vasodilation, secretion, and mucosal immune cell function are well-studied, the direct impact of VIP on intestinal epithelial cell turnover and differentiation remains less understood. Intestinal stem and progenitor cells are essential for the maintenance of intestinal homeostasis and regeneration, and their functions can be modulated by factors of the stem cell niche, including neuronal mediators. Here, we investigated the role of VIP in regulating intestinal epithelial homeostasis and regeneration following irradiation-induced injury. Methods Jejunal organoids were derived from male and female C57Bl6/J, Lgr5 -EGFP-IRES-CreER T2 or Lgr5 -EGFP-IRES-CreER T2 / R26 R-LSL-TdTomato mice and treated with VIP prior to analysis. Injury conditions were induced by exposing organoids to 6 Gy of irradiation (IR). To investigate protective effects of VIP in vivo, mice received 12 Gy of abdominal IR followed by intraperitoneal injections of VIP. Results We observed that VIP promotes epithelial differentiation towards a secretory phenotype predominantly via the p38 MAPK pathway. Moreover, VIP prominently modulated epithelial proliferation as well as the number and proliferative activity of Lgr5-EGFP + progenitor cells under homeostatic conditions. In the context of acute irradiation injury in vitro, we observed that IR injury renders Lgr5-EGFP + progenitor cells more susceptible to VIP-induced modulations, which coincided with the strong promotion of epithelial regeneration by VIP. Finally, the observed effects translate into an in vivo model of abdominal irradiation, where VIP showed to prominently mitigate radiation-induced injury. Conclusions VIP prominently governs intestinal homeostasis by regulating epithelial progenitor cell proliferation and differentiation and promotes intestinal regeneration following acute irradiation injury.